Hourly forecast data of near-surface and surface fields for the wintertime period 15 October 2019 to 15 March 2020 at the location of the Multidisciplinary drifting Observatory for the Study of Arctic Climate expedition from 7 operational and quasi-operat - Solomon, Amy; Bazile, Eric; Day, Jonathon; Frank, Helmut P; Remes, Teresa; Tolstykh, Mikhail; Doyle, James D (PANGAEA, 2025)
Hourly forecast data of near-surface and surface fields for the wintertime period 15 October 2019 to 15 March 2020 at the location of the Multidisciplinary drifting Observatory for the Study of Arctic Climate expedition (MOSAiC; which drifted from the Siberian Sea to Fram Strait from October 2019 to October 2020, see Shupe et al., 2022) from 7 operational and quasi-operational forecast systems; the NOAA-PSL Coupled Arctic Forecast System (CAFS; Solomon et al., 2024), the ECMWF Integrated Forecast System (IFS; Haiden et al., 2019), the Météo-France ARPEGE-GELATO forecast system (ARPEGE; Bazile et al., 2020), the Russian Hydrometcentre SL-AV forecast system (SL-AV; Tolstykh et al., 2018), the German Weather Service forecast system (DWD; Zängl et al., 2015), the experimental configuration of the HARMONIE-AROME forecast system (H-AROME; Bengtsson et al., 2017), and the U.S. Navy-ESPC forecast system (NAVY; Barton et al., 2021). These forecasts were produced for the intercomparison study of wintertime statistics of the surface energy budget by Solomon et al. (2023) and used by Sledd et al. (2024) to study the response of the surface energy balance to changes in radiative forcing. See the metadata section for a detailed description of all fields included in the files.
Keywords: forecasts; MOSAiC expedition; sea ice-atmosphere interactions; surface energy balance